Spectral properties and complex formation with Cu2+ ions of 2-and 4-(N-arylimino)-quinolines - Posokhov, Y; Kus, M; Biner, H; Gümüs, MK; Tugcu, FT; Aydemir, E; Kaban, S; Içli, S (ELSEVIER SCIENCE SA, 2004)
The spectral-fluorescent properties of substituted 2- and 4-(N-arylimino)quinolines have been investigated in solvents of different polarity and proton donating ability, and in immobilized phases of PVC films and sol-gel matrix. The effect of the solvent on spectral characteristics has been estimated. It has been shown that, despite the possibility of quenching process linked with intramolecular motions with great amplitude of the non-fixed azomethine fragment, the low fluorescence quantum yield of the studied compounds in polar solvents and in immobilized phases is caused mainly by the quenching process which is not linked directly with significant changes in molecular geometry. The complexation process of the studied ortho-hydroxyphenols with Cu2+ ion caused strong changes in their absorption spectra. Among the studied compounds, 4-chloro-2-[(quinolin-2-yl-methylene)]-amino-phenol has shown better selectivity and sensitivity towards Cu2+. This compound could be suggested as a prospective reagent for spectroscopic determination Of Cu2+ trace amounts (<10(-4) M), e.g. for copper determination in Al-based alloys. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: spectral-fluorescence properties; fluorescence quenching; complex formation; FLUORESCENCE; COPPER; ACID; Chemistry